STRATEGI PENGEMBANGAN PARIWISATA DI SEPANJANG PEMBANGUNAN JALUR LINTAS SELATAN (JLS) DI KECAMATAN PANGGUL KABUPATEN TRENGGALEK (WAKTU: Jurnal Teknik UNIPA, 2025)
This research aims to identify strategies for developing the Southern Cross Route in Panggul District, Trenggalek Regency. The analysis methods used in this research are qualitative descriptive for the first problem formulation and SWOT analysis for the second problem formulation. The data collection methods used include observation, questionnaires, institutional surveys, and interviews. This research identifies tourism potential in Panggul District, supported by natural beauty and local cultural richness. The SWOT analysis results show a Strengths - Weaknesses score of -0.80 and an Opportunities - Threats score of -0.20, indicating a position in quadrant III. These findings provide a basis for developing strategies that can enhance the appeal and sustainability of tourism in the area.The tourism development strategy along the Southern Cross Route should focus on several key points. First, strengthening spatial planning regulations. Second, increasing local community involvement through education and training will empower them as key players in the tourism industry. Third, the utilization of supporting attractions, such as biodiversity and local culture, should be carried out in a sustainable manner.